020 Comparison of fractional flow reserve measurements obtained using central vs distal peripheral intravenous adenosine infusion to induce hyperaemia. (16th May 2012) - Sirker, A; Paul, G; Dworakowski, R; Melikian, N; Byrne, J
Abstract : Introduction: Measurement of fractional flow reserve (FFR) permits physiological evaluation of coronary lesions. Maximal hyperaemia is required and adenosine is most often used for this. The gold standard method is continuous adenosine infusion via a large central (usually femoral) vein. Use of radial access for coronary angiography is now used in over 50% of cases performed in the UK. Hence it is desirable to have an alternative route for adenosine delivery. Peripheral venous access is frequently obtained in the hand, since veins are often most readily accessible here. However concerns exist as to whether delivery from this site would achieve adequate vasodilatation. Our aim was to address this question. Methods: Ethical approval and informed consent was obtained. Subjects were selected from patients attending for coronary angiography who were deemed to need a pressure wire to assess an intermediate coronary stenosis. Subjects received intravenous adenosine infusion sequentially by two routes: first, via a 20G hand cannula, and then, after a washout period, via a 6F femoral venous sheath. Adenosine was administered at 140 μg/kg/min for each site. Data interpretation was performed in a blinded manner. Baseline values of FFR were recorded, as was the minimal FFR achieved with adenosine infusion, from each infusion site. Time to peak hyperaemia was also recorded separately for each infusion site. Results: 37 coronary artery lesions were evaluated in 23 patients. For the overall group, FFR using hand vein adenosine infusion was 0. 86±0.09; FFR using femoral vein adenosine infusion was 0.85±0.09. Individual paired comparisons of FFR readings using the different routes of adenosine administration are shown in Abstract 020 figures 1 and 2 below. Abstract 020 figure 1 shows FFR using hand vein for adenosine vs FFR using femoral (groin) vein for adenosine—paired data are shown as (x, y) points. The line of unity is shown for a theoretical perfect agreement between the measures. Abstract 020 figure 2 shows a Bland Altman plot of FFR derived from hand vs groin adenosine infusions. The mean difference between the two measures of FFR was 0.007 with a SD of 0.020. The 95% limit of agreement extended from −0.031 to +0.046. Using a threshold for ischaemia of FFR ≤0.75, there were no cases in which use of hand vein adenosine would have misclassified a lesion compared to the "gold standard" central vein adenosine. Using a threshold for ischaemia of FFR ≤0.80, there was one case which would have been classified differently. Time to maximal hyperaemia was significantly greater with hand vein adenosine infusion. (75.7±32.8 s vs 40.5±10.3 s, p<0.001 on t test). Conclusion: The use of hand vein adenosine infusion produced very similar values of minimum FFR to those using femoral vein adenosine. These data have important practical implications for patients undergoing transradial procedures who require FFR assessment.